Tendency of Investment Economy Formation - Battalova, Alina R.; Tukhvatullin, Ruslan Sh.; Mukhametgaliev, Farit N.; Mukhametgalieva, Farida F.; Sitdikova, Landish F. (International Journal of Criminology and Sociology, 2022)
The relevance of the topic is caused by the need to identify trends and characteristics of the investment economy formation in the face of the external economic environment new challenges. The article’s main aim is to develop recommendations for optimizing the directions of the state economic policy in the field of investment activity development. The research is based on an analysis of the current situation and the identification of trends in the formation of Russia’s investment economy and its regions. The study’s novelty is to identify trends and characteristics in the investment economy formation in the regions of Russia and formulate development sectors in the Republic of Tatarstan. The main results of the study are as follows: issues of the preconditions for the formation of investment activity in the country’s economy are examined, as well as macroeconomic indicators that form the financial foundations of the investment economy, the main directions for improving investment attractiveness are identified and proposed, including the use of the advantages of geographical and geopolitical position, increasing the economic, social and political level of development, improving the state of the environmental situation and demographic situation.